Dynamics of Higher Education for Accountants in Russia: Achievements, Problems and Prospects - T. Yu. Druzhilovskaya; E. S. Druzhilovskaya (Высшее образование в России, 2023)
Intensive changes in business under the influence of the scientific and technological revolution cause significant changes in the requirements for the accounting profession and challenge society to look for new approaches to university accounting education. This study examines problematic and unresolved issues of Russian higher accounting education. Authors explore the history of reform over the past 30 years and the current state to find the best future directions for the development of accounting education in Russia. The research purpose is to identify causal relationships that affect the dynamics of Russian accounting education. Authors determine events that have had the greatest impact on the change in approaches to Russian accounting education. These events include accounting reform in accordance with the requirements of a market economy, information technology development, the inclusion and exit of Russia in the Bologna process, and Russia’s support for the creation of International Education Standards (IESs). Authors examine how Russian accounting education has changed under the influence of these events and find that there are both positive and problematic aspects related to the changes that have occurred in Russian accounting education. Authors show that there are both positive effects and problems from the introduction of a two-level higher accounting education in Russia (bachelor’s and master’s levels) and the convergence of the Russian Education Standards with the International Education Standards. To find solutions to the current problems of Russian accounting education, authors explore statistical data on the requirements of modern Russian business for the profession of an accountant and analyze the results from the survey of university graduates aimed at studying the degree of their satisfaction with the higher accounting education received. Based on this study, there are determined the prospects for improving Russian accounting education and substantiated the recommendations for its further development. These recommendations will be useful for organizing accounting education in economic universities, as well as for developers of economic education standards. The developed recommendations contribute to the reform of higher economic education, since many of them can be used to teach not only accountants, but also other economic professions.